Relationship between Self-Administered Cues and Rehabilitation Outcomes in Individuals with Aphasia: Understanding Individual Responsiveness to a Technology-Based Rehabilitation Program - Des Roches, Carrie A.; Mitko, Annette; Kiran, Swathi (Frontiers in Human Neuroscience, 2017)
An advantage of rehabilitation administered on computers or tablets is that the tasks can be self-administered and the cueing required to complete the tasks can be monitored. Though there are many types of cueing, few studies have examined how participants’ response to rehabilitation is influenced by self-administered cueing, which is cueing that is always available but the individual decides when and which cue to administer. In this study, participants received tablet-based rehabilitation where the tasks were self-paced and remotely monitored by a clinician. The results of the effectiveness of this study were published previously (Des Roches et al., 2015). The current study looks at the effect of cues on accuracy and rehabilitation outcomes. Fifty-one individuals with aphasia completed a 10-week program using Constant Therapy on an iPad targeted at improving language and cognitive deficits. Three questions were examined. The first examined the effect of cues on accuracy collapsed across time. Results showed a trend where the greater the cue use, the lower the accuracy, although some participants showed the opposite effect. This analysis divided participants into profiles based on cue use and accuracy. The second question examined how each profile differed in percent cue use and on standardized measures at baseline. Results showed that the four profiles were significantly different in frequency of cues and scores on WAB-R, CLQT, BNT, and ASHA-FACS, indicating that participants with lower scores on the standardized tests used a higher percentage of cues, which were not beneficial, while participants with higher scores on the standardized tests used a lower frequency of cues, which were beneficial. The third question examined how the relationship between cues and accuracy was affected by the course of treatment. Results showed that both more and less severe participants showed a decrease in cue use and an increase in accuracy over time, though more severe participants continued to used a greater number of cues. It is possible that self-administered cues help some individuals to access information that is otherwise inaccessible, even if there is not an immediate effect. Ultimately, the results demonstrate the need for individually modifying levels of assistance during rehabilitation.